Inisiatif Pariwisata Pro Poor di Kawasan Wisata Lagoi: Sebuah Studi Empiris Rantai Nilai Makanan - Hary Jocom; Minarni Anita Romaida Gultom (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This study aims to identify the tourism value chain and its contribution to improving the local community's economy, especially in the food supply chain of 10 hotels/resorts in the Lagoi tourism area, Bintan Regency, Riau Archipelago Province. This study uses a qualitative method related to the food supply chain consisting of vegetables & fruits, fish & seafood, poultry and meat. This study uses primary data through semi-structured interviews with sources from hotel/resort managers, collectors, farmers, fishermen, traders, and suppliers. Foodstuff transaction data obtained directly from the sources. Secondary data obtained from reports by related sources. The results of this study indicate that the existence of the Lagoi tourism area contributes to the economic turnover of the people in Bintan. This shows that all food needs for hotels/resorts are supplied by local economic actors, i.e., supplied by business actors in the agriculture, fish/seafood, poultry and local meat sectors. Local suppliers have become the priority for hotels/resorts. When the requested item cannot be obtained, hotels/resorts will seek it from outside of Bintan. The economic impact is felt directly by producers, be they farmers or fishermen. However, the four sectors mentioned above, the fish/seafood supply chain has a high economic value compared to others, so that it has a broad and real impact, especially for fishermen and related stakeholders. This is shown by the image that Bintan is an archipelago that has a wealth of marine products, supported by various beach and sea destinations that attract tourists to enjoy the processed marine products.